Vpliv epidemije COVID-19 na telesno dejavnost in splošno počutje pri rekreativno telesno dejavnih odraslih - Colja, Evelin (Šport (Ljubljana), 2021)
Coronavirus-19 pandemic led to lockdown of public life and consequently forced a close down of all forms of organised recreational physical activity. The aim of this study was to determine the changes of physical activity and sedentary behaviour during the COVID-19 epidemic in physically active adults. In this retrospective study we included 233 participants, aged between 18 to 65 years. Participants completed a questionnaire consisted of questions related to physical activity and general well-being prior to epidemic and during epidemic. During the epidemic, there was a decrease in vigorous physical activity (-1328 METs min/week, p<0.001), moderate physical activity (-480 MET min/week, p <0.001) and total weekly physical activity (-1873 MET min/week, p<0,001), and an increase in weekly sedentary behaviour (+4 h per day, p<0,001). In men, we found a greater decline in total weekly physical activity during the epidemic than in women (-350 MET min / week, p = 0.021), with no differences between age groups (p = 0.394). Worse general well-being during the epidemic was associated with declined physical activity (p<0,001). Our results demonstrated a decrease in physical activity during the epidemic in recreational physically active adults and show the need to restructure current organized forms of physical activity for upcoming waves of COVID-19 epidemic.
Keywords: COVID-19; epidemic; epidemije; general well-being; measures; physical activity; splošno počutje; sport; šport; telesna dejavnost; ukrepi